1991
DOI: 10.1128/jvi.65.12.6735-6742.1991
|View full text |Cite
|
Sign up to set email alerts
|

A discrete cis element in the human immunodeficiency virus long terminal repeat mediates synergistic trans activation by cytomegalovirus immediate-early proteins

Abstract: The major immediate-early (IE) promoter of human cytomegalovirus directs the expression of several differentially spliced and polyadenylated mRNAs that encode isoformic proteins with apparent molecular masses of 55, 72, and 86 kDa. All of these proteins are potent transcriptional regulatory proteins. We are interested in the collateral interactions between human cytomegalovirus and human immunodeficiency virus (HIV) in the context of dual infection of a cell. The roles of the specific IE protein isoforms and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
45
1

Year Published

1993
1993
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 51 publications
2
45
1
Order By: Relevance
“…IE1-72, IE2-55, and IE2-86 are important transcriptional regulators with multiple functions essential for subsequent viral and cellular gene expression and viral replication. IE1-72 stimulates transcription from HCMV promoters as well as heterologous viral and cellular TATA and TATA-less promoters (6,9,16,25,30,36,53,82,86,87). The mechanism of IE1-72 transactivation may involve the induction of NF-B (16,75) or other, unknown processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IE1-72, IE2-55, and IE2-86 are important transcriptional regulators with multiple functions essential for subsequent viral and cellular gene expression and viral replication. IE1-72 stimulates transcription from HCMV promoters as well as heterologous viral and cellular TATA and TATA-less promoters (6,9,16,25,30,36,53,82,86,87). The mechanism of IE1-72 transactivation may involve the induction of NF-B (16,75) or other, unknown processes.…”
mentioning
confidence: 99%
“…IE2-86, on the other hand, is a DNA-binding protein with at least five described DNA binding sites (2,18,48,56,60,76). IE2-86 is a promiscuous transactivator of both viral and cellular promoters (9,23,30,35,36,41,53,59,64,69,76,84,87) and may transactivate many of these promoters by associating with the TATA-binding protein within the basal transcription component, TFIID (11,27,35,48,49,59,79). In addition, IE2-86 synergizes with IE1-72 in transactivating a variety of promoters (24,30,36,41,53,59,64,82,84,87) and autorepresses its own promoter (15,40,58,60,(67)(68)(69)82).…”
mentioning
confidence: 99%
“…The 86-kDa IE-2 protein is a transactivator of a number of homologous as well as heterologous promoters (14,25,31,43). For IE-1, there is evidence for an independent role in the activation of heterologous promoters such as the human immunodeficiency virus type 1 long terminal repeat or the hsp7O promoter (4,13,14,47). Its influence on early promoters of HCMV seems to be rather low.…”
mentioning
confidence: 99%
“…Subsequently, numerous studies have further examined the role of the MIE gene products in transactivation of the HIV-1 and HIV-2 L T R s .~' -~~ The majority of these studies involved gene transfer experiments using effector plasmids based on genomic fragments encompassing either IE-I or IE-2 or Consistently, such assays demonstrate that co-transfection of a plasmid expressing IE-2 activates the HIV-LTR. [70][71][72][73][74][75][76][77][78][79] In contrast, co-transfection assays to score for the activating capacity of the IE-I protein(s) are controversial and have been reported to have either no e f f e~t ,~"~~,~~ an upregulatory effect,76r78f79 or even an inhibitory effect upon HIV-LTR f~nction.~' However, in those cases in which IE-1 alone demonstrated either negligible or up-regulatory effects, it acted in concert to synergistically augment HIV-LTR directed expression when co-expressed with IE-2.70,7&79 The reason for these apparently contradictory results for IE-1 function is not readily apparent. The variations may possibly reflect the different expression vectors and consequently the level of expression of the IE proteins, different cell-types or even different transfection protocols utilised in the various studies.…”
Section: Activating Capacities Of the Various Mie Proteinsmentioning
confidence: 99%
“…Recently, the availability of cDNA clones corresponding to the various IE proteins has greatly facilitated the identification of protein products responsible for mediating the specific activity that had previously been ascribed to IE regions 1 and 2.78r79 These studies have clearly shown the importance of IE72 (IE-I) and IE86 (IE-2) as the major IE proteins responsible for independently stimulating HIV directed expre~sion,~',~~ while only marginal activation by IE55 (IE-2) protein was observed.78 Further, it was demonstrated in dual co-transfection assays that the IE55 isoform non-cooperatively influenced the IE72 or IE86 proteins in stimulating the HIV-LTR. 78 In contrast, the IE72 and IE86 proteins synergistically influenced each other in activating the LTR.78r79 As described above, the IE55 protein is an isoform variant of the IE86 protein that differs by a 155amino-acid deletion between residues 365 and 519 of IE86. The finding that IE55 does not functionally synergise with IE72 implicates the specific domain unique to IE86 in the synergic response.…”
Section: Activating Capacities Of the Various Mie Proteinsmentioning
confidence: 99%